Graphene oxide/oxidized carbon nanofiber/mineralized hydroxyapatite based hybrid composite for biomedical applications. (13th December 2017) - Murugan, N; Sundaramurthy, Anandhakumar; Chen, Shen-Ming; Sundramoorthy, Ashok K
Abstract: Hydroxyapatite (Ca10 (PO4 )6 (OH)2, HAP), a multi-mineral substituted calcium phosphate is the main mineral component of tooth enamel and bone, has become an important biomaterial for biomedical applications. However, as-synthesized HAP has poor mechanical properties and inferior wear resistance, so it is not suitable to use in bone tissue engineering applications. We report the successful incorporation of oxidized carbon nanofibers (O-CNF) and graphene oxide (GO) into the mineralized hydroxyapatite (M-HAP) which showed excellent mechanical and biological properties. GO improved the high mechanical strength and corrosion protection of the substrate in simulated body fluid (SBF) solution and promoted the viability of osteoblasts MG63 cells. As-prepared M-HAP/O-CNF/GO composite showed materials characteristics that similar to natural bone (M-HAP) with high mechanical strength. The resultant M-HAP/O-CNF/GO composite was characterized out by x-ray diffraction (XRD), field-emission scanning electron microscopy (FE-SEM), and Fourier-transform infrared spectroscopy (FT-IR), respectively. The mechanical strength of the material was determined by Vicker's micro-hardness method and it was found that M-HAP/O-CNF/GO (468 ± 4 Hv) composite has superior mechanical properties than M-HAP (330 ± 3 Hv) and M-HAP/GO (425 ± 5 Hv) samples. In addition, antibacterial activity of the composite was studied against Staphylococcus aureus and Escherichia coli . Furthermore, the cell viability of the composite was observed in vitro against osteoblast cells. All these studies confirmed that the M-HAP/O-CNF/GO composite can be considered as potential candidate for dental and orthopedic applications.